2021
DOI: 10.1186/s42238-021-00071-3
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use frequency, route of administration, and co-use with alcohol among older adults in Washington state

Abstract: Background The US national surveys and data from legal adult use cannabis states show increases in the prevalence of cannabis use among older adults, though little is known about their manner of cannabis consumption. Here, we examine cannabis use frequency, routes of cannabis administration, and co-use with alcohol, focusing on adults aged 50–64 and ≥65. Methods Data come from a general population survey conducted January 2014–October 2016 (N=5492)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A more recent study that focused on a general population survey in Washington state found that among older adults who use cannabis, an estimated 50.8% of those aged 50–64 and 41.5% of those aged ≥65, “usually” or “always” co-use cannabis with alcohol. Furthermore, they found that among men aged ≥65, frequent cannabis use was positively associated with the use of alcohol ( Subbaraman & Kerr, 2021 ). While older adults have a lower total estimated prevalence of concurrent cannabis and alcohol than young adults or middle-aged adults, recent data suggest that this behavior may be increasing.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study that focused on a general population survey in Washington state found that among older adults who use cannabis, an estimated 50.8% of those aged 50–64 and 41.5% of those aged ≥65, “usually” or “always” co-use cannabis with alcohol. Furthermore, they found that among men aged ≥65, frequent cannabis use was positively associated with the use of alcohol ( Subbaraman & Kerr, 2021 ). While older adults have a lower total estimated prevalence of concurrent cannabis and alcohol than young adults or middle-aged adults, recent data suggest that this behavior may be increasing.…”
Section: Introductionmentioning
confidence: 99%
“…4 Even though there is little evidence that adult patients consume cannabis, its consumption in an older population aged ≥ 50 years has been elevated from 15.1% in 2014 to 23.6% in 2016 since legalization for medical use encourages former non-users to start using it. 5 In the United States, the utilization of cannabis is increasing for medical and recreational purposes while the potential risk is declining. [6][7][8] Even though there is little knowledge of the risks and advantages of it, they primarily utilize it to control the symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, the global cannabis user population was over 4%, and nearly 6% among ages (3). Intriguingly, its consumption in population aged ≥ 50 years has been elevated from 15.1% in 2014 to 23.6% in 2016 since legalization for medical use encouraged former non-users to start using it (4). With an expansion of legalized countries, more research studies are being explored on its potential therapeutic effects and adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%